Media interview techniques a complete guide to media training - Taylor, Robert 1968- (London Kogan Page, 2016)
"A practical guide to preparing for, conducting, and evaluating the success of media interviews, this book is based on communications expert Robert Taylor's eight-step methodology for polished and confident interview delivery across a range of platforms--TV, radio, internet, and video. Taylor explains how to handle nerves, voice and body language, communicate in a crisis, answer unfair questions, know when to decline interviews, win over skeptical audiences, and create a resonant message"--Provided by publisher.
Why do a media interview? -- Have something newsworthy to say! -- When to decline a media interview -- Summary -- Exercises-- Preparing for your interview -- Basic information you need -- Anticipate the questions -- Know your organization's line on sensitive corporate issues -- What's topical in your industry that the journalist might ask you about? -- The role of your PR department -- Become a great spokesperson -- Get media trained -- Summary -- Exercises -- How to create a resonant message -- Make your business objective action-oriented -- No more than three key messages -- Constructing a 'message sandwich' -- Get to the point... -- Remembering your messages -- Summary -- Exercises -- Keeping your cool -- Too much adrenaline - nervousness -- Too much adrenaline - anger -- So should you ever lose your cool? -- The exceptions -- Not enough adrenaline - over-confidence -- What's better: live or recorded? -- Summary -- Exercises -- Voice and body language -- Eye contact -- Posture -- Pace of delivery -- Other aspects of good voice and body language -- Dress sense -- Summary -- Exercises The perfect tone of voice -- A W.I.S.E tone -- Keeping your delivery as conversational as possible -- Using mind pictures -- All elements of wise working together -- Curtailing your curtness -- Finding the full stop -- Humour -- Summary -- Exercises -- Keeping control of the interview -- ABC: the bridging technique -- The helicopter technique -- The caving technique -- Avoiding the question - rarely a good idea -- Repetition of key messages -- How to get off to a good start in a live broadcast interview -- Handling unfair questions -- The honest truth -- Apologising -- Getting your company name into a broadcast interview -- Off the record -- Summary -- Exercises08 Winning over sceptical and hostile audiences -- The spectrum of opinion -- Bridges of empathy -- Cooling things down -- Empathy must be genuine -- Attentive listening -- Empathy as a message -- The 'open sandwich' - starting with your example or evidence then hitting the key message -- Insulting, offending and patronizing people -- Empathy in politics -- Does empathy work everywhere? -- Summary -- Exercises09 Crisis media interviews -- How not to handle a crisis media interview -- 'I'd like my life back' -- A formula for handling crisis interviews -- Concern/sympathy -- Action/explanation -- Concern and action working together -- Perspective -- Being ambushed or 'doorstepped' -- Summary -- Exercises -- Capitalizing on your interview -- Analyse what went well and not so well -- Use social media to ensure your interview is seen, heard or read by your target publics -- And if you don't like something the journalist wrote? -- Build a strong relationship with the journalist -- Summary -- Exercises.
Includes bibliographical references (pages 199-201) and index.
Keywords: Interviewing in mass media; Public relations